Pathologically expanded peripheral CD4+PD‐1+Foxp3− T‐cell subset promotes B‐cell hyperactivity in patients with rheumatoid arthritis - Ziran Bai; Rui Liu; Jiaqing Liu; Cheng Zhang; Zilong Wang; Jingjing Qi; Yawei Tang; Xia Li (Rheumatology & Autoimmunity, 2024)
Abstract Background Rheumatoid arthritis (RA) is an autoimmune disease characterized by destructive polyarthritis, and abnormal T–B‐cell interactions may contribute to its pathogenesis. This study aimed to investigate the characteristics and roles of CD4+ programmed death 1 (PD‐1)+Foxp3− T cells in relation to the B‐cell response in patients with RA. Methods This study included 155 patients with RA and 36 age‐ and sex‐matched healthy controls (HCs) from the Second Hospital of Dalian Medical University in China. Flow cytometry was used to assess the proportion and properties of peripheral CD4+PD‐1+Foxp3+ T cells, including their proliferation, activation, cytokine production, and capacity to induce B‐cell differentiation. Results The proportion of CD4+PD‐1+Foxp3− T cells was increased in patients with RA compared with HCs ([10.78 ± 0.60]% vs. [5.67 ± 0.40]%, p < 0.001), and this was positively associated with the B‐cell response. Compared with CD4+PD‐1+Foxp3+ T cells, CD4+PD‐1+Foxp3− T cells from patients with RA exhibited increased expression of Ki67 ([6.52 ± 0.41]% vs. [3.87 ± 0.42]%, p < 0.01) and activation markers, produced higher levels of cytokines, and showed enhanced B‐cell differentiation. Furthermore, anti‐interleukin‐6R antagonists decreased the proportion, activation, and cytokine production of CD4+PD‐1+Foxp3− T cells in vitro. The frequency of type 2 CD4+PD‐1+Foxp3− T cells was significantly higher in patients with RA than that in HCs ([37.27 ± 1.43]% vs. [29.05 ± 1.30]%, p < 0.05). Conclusions Peripherally expanded CD4+PD‐1+Foxp3− T cells in patients with RA, which induced B‐cell hyperactivity, may be inclined toward type 2 helper T cells. Our findings revealed a novel T‐cell subset that contributes to B‐cell hyperactivity in the pathogenesis of RA.